STEM students’ English language learning strategies and underlying factors pertaining to open distance learning - Ahmad Ghulamuddin, Nurul Jannah; Tengku Sharif, Tengku Intan Suzila; Abdul Rahman, Zainurin (Universiti Sultan Zainal Abidin, 2022)
Background and Purpose: The COVID19 pandemic challenges on learning necessitate the understanding of students’ Language Learning Strategies (LLS). Studies on science, technology, engineering, and mathematics (STEM) students’ English LLS is scarce. The objectives of the study are to examine the LLS employed by STEM students learning English as a second language (ESL) in a public university (PU) in Malaysia and to investigate the LLS underlying factors pertaining to the open distance learning (ODL). Methodology: This study was designed as survey research, employing the quantitative approach to gather data. The Strategy Inventory of Language Learning (SILL) questionnaire was administered to 250 engineering undergraduates as respondents, who were chosen using a purposive sampling method. Data were analyzed descriptively using the Statistical Package for Social Sciences (SPSS) version 21.0. The Principal Component Analysis (PCA) with varimax rotation was conducted to determine the construct validity. PCA appropriateness was suggested by the inter-item correlation. Findings: The compensation, metacognitive and cognitive learning strategies were the most frequently used strategies while the memory and affective strategies were the least. The PCA added vital information like the memory strategy corresponds to the metacognitive strategy. The cognitive strategy concept of ‘practice,’ may demand a revisit to some traditional grammar learning methods. There are also demands for social-emotional factors to be considered. ODL has imposed bigger demands too. Contributions: The findings may assist ESL educators to boost STEM students’ self-monitoring behavior, to plan and coordinate their own learning process. PCA’s ‘Self-Awareness’ concept revealed that policy makers need to conduct more training to ensure executions run smoothly.